Crowd simulation with smart objects and inference engine - Tan, Debbie Su Li. (2009)
Crowd behaviour modelling and simulation has become more essential for the purpose of military training. This report seeks to detail the creation of an informed environment with the adoption of Urban Environment Model (UEM) and Smart Objects to model a train station in Singapore Context. To model a realistic and dynamic system, this project – an extension of the COSMOS project, explores the use of rule engine to model varying population compositions with time, of which a population make-up will interact differently with objects. The resulting scenario-based COSMOS system is capable of providing flexibility in changing scenarios by simply having different behaviour rule files. The adaptability provided by this system may be seen in experiments conducted in this report.